Aphaenogaster gamagumayaa sp. nov.: the first troglobiotic ant from Japan (Hymenoptera: Formicidae: Myrmicinae) - Naka, Takeru; Maruyama, Munetoshi (Zootaxa, 2018)
Aphaenogaster gamagumayaa sp. nov., a new troglobiotic (true cave-dwelling) ant species, from a limestone cave on the island of Okinawa (Okinawa-jima), Ryukyu Archipelago, Japan is described. This is the first discovery of a troglobiotic ant in Japan and the second verified record worldwide. This species has only been found in a cave area with heavy guano deposits, and some worker ants were observed carrying guano. The evidence for categorizing this new species as troglobiont is discussed.